Acute Kidney Injury in Lymphoma: A Single Centre Experience. (3rd February 2014) - Khalil, Muhammad Abdul Mabood; Latif, Hira; Rehman, Abdur; Kashif, Waqar Uddin; Awan, Safia; Khalil, Zarghona; Mushtaq, Uziar; Ahmad, Maria; Khalil, Muhammad Ashhad Ullah; Ranga Sami, Manickam; Tan, Jackson
Abstract : Background . Acute kidney injury (AKI) is a common but least studied complication of lymphoma. Objective . To determine the frequency and predictors of AKI in lymphoma and to study the impact of AKI on hospital stay and mortality. Methods . Retrospective review of medical records of hospitalized lymphoma patients aged ≥14 years between January 2008 and December 2011 was done. Results . Out of 365 patients, AKI was present in 31.8% (116/365). Multivariate logistic regression analysis showed that independent predictors for AKI included sepsis (odds ratio (OR) 3.76; 95% CI 1.83–7.72), aminoglycosides (OR 4.75; 95% CI 1.15–19.52), diuretics (OR 2.96; 95% CI 1.31–6.69), tumor lysis syndrome (OR 3.85; 95% CI 1.54–9.59), and R-CVP regimen (OR 4.70; 95% CI 1.20–18.36). AKI stages 2 and 3 was associated with increased hospital stay (OR 2.01; 95% CI 1.19–3.40). Conclusion . AKI was significantly associated with sepsis, aminoglycoside, diuretics, presence of tumor lysis syndrome, and use of R-CVP regimen. Presence of AKIN (Acute Kidney Injury Network) stages 2 and 3 AKI had increased hospital stay. AKI was also associated with increased mortality.